The Effectiveness of Wordwall in Improving Pronunciation, Stress Placement, and Intonation for B2-Level English Psychology Students: An Experimental Case Study at a Georgian University - Makharashvili, Mari (European Scientific Journal, ESJ, 2025)
This paper focuses on examining the effectiveness of the Wordwall online game application in improving pronunciation, stress placement, and intonation for B2-level English for Psychology students. An experimental approach using quantitative methods was employed to gather statistically reliable data. Sixty Georgian university students participated, with 30 in the experimental group (using Wordwall) and 30 in the control group (using traditional methods). Students recorded 10 challenging words using smartphones and computers and submitted them to the researcher before and after a semester of learning. The recordings were evaluated using a rubric, and data were analyzed with SPSS 24.00. Statistical analysis, using the Wilcoxon Signed-Rank and Mann-Whitney U Test, showed significant improvements in pronunciation and intonation in the experimental group (p-value < 0.05). Positive feedback from students highlighted Wordwall’s effectiveness. The findings suggest that game-based learning is a valuable tool for improving language skills.